'We Are Left with Barely Anything': Colonial Rule, Dependency, and the Lever Brothers in the Belgian Congo, 1911–1960. Issue 1 (2nd January 2020) - Loffman, Reuben; Henriet, Benoît
ABSTRACT: When historians have examined labour relations in the Belgian Congo, the paradigmatic image is that of rapacious, avaricious metropolitan investors oppressing helpless African communities by dint of a skeletal but violent cohort of intermediaries. Leopold II was exemplary of this trend. Having never set foot in the Congo, he drew vast profits from the territory by means of initiating a series of appalling atrocities as his employees coerced Africans into harvesting rubber in the late nineteenth and early twentieth centuries. Such emphasis on exploitation fits with a long-standing scholarly emphasis on African dependency that has also highlighted how capital has leaked out of the Congo and into Europe and North America. Yet this article argues, first, that capital sometimes leaked from Europe to the Congo. Secondly, this essay suggests that not every investor in the Congo was as mendacious and cynical as Leopold II. Some, namely the Lever brothers, came to the Congo in the sincere hopes of establishing Christian, middle class African communities in the bush. But Lever's plans were compromised by the firm's paternalism and their overriding need to turn a profit.